Geriatric health related problems in an urban area of southern Rajasthan - Mangal, Nitesh; Kumar L., Dilip; Varghese, K. A.; Chauhan, Meet; Samanta, Matariswa (International Journal Of Community Medicine And Public Health, 2019)
Background: There is a paradigm shift in the social values towards the elderly people due to urbanization and higher educational linked migration. Consequently, problems like loneliness, lack of emotional support, economic insecurities are faced by the elderly population. The objectives of the study were to assess the socio-economic dimensions and to examine the morbidity and mortality patterns of elderly persons in the study area. Methods: A cross- sectional study was conducted among 536 elderly persons from May to August 2019 in an urban area of Udaipur. A pre-structured and pre-tested questionnaire was used to collect information on socio-demographic details, morbidity profile and socio-economic problems of elderly persons. The data was analyzed using class frequencies, ‘t’ test for equality of gender difference in mortality ages and Chi-square test for association of age class with morbidity. Results: A majority of study subjects were females (52.05%). There was significant difference in proportions of elderly male and female persons across their educational levels. The chi-square test for association of age classes with number of health problems revealed significant association. About 56.34% of 536 elderly people were leading an unsatisfactory life. Conclusions: The major morbidities included arthritis, hypertension, diabetes, cataract, dental problems, cardiovascular problems etc. Financial problems were more severe among elderly. The availability of trained paramedical professionals for home care and day care units and legal bindings on family members for safety and security of elderly person can be effective measures to overcome the problems being faced by them.